“THE IMPACT OF BEHAVIORAL BIAS ON INVESTMENT DECISION ON THE BASIS OFEXPERIENCE OF INVESTOR” (CAHIERS MAGELLANES-NS)
Abstract: The study titled "The impact of behavioral bias on investment decision on the basis if experience of investor” rigorously examines the pervasive influence of behavioral biases on investment decision-making within the context of the experience of the investor. This study delves into the variations in biases across investors of different experience levels. The analysis presented in this chapter stems from data gathered through a structured questionnaire distributed among 450 investors operating in the tricity region (Chandigarh, Mohali, and Panchkula). By examining the responses collected, insights into how biases manifest differently depending on the investors' levels of experience are sought.